STEM PjBL Sparks Global Ecoliteracy Advancement: STEM PjBL Memicu Kemajuan Ekoliterasi Global - Indrasari, Ayu; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2024)
This study examines the impact of a STEM-based Project-Based Learning (PjBL) model on Class VIII students' ecoliteracy abilities at SMP Negeri 1 Tanggulangin using a quantitative pre-experimental approach. The research design employs a One Group Pretest-Posttest Design with non-probability purposive sampling. Results from administering valid ecoliteracy tests and analyzing data with the N-Gain Test and One Way ANOVA reveal a significant increase in ecoliteracy abilities after implementing the STEM-based PjBL model, indicating its effectiveness in enhancing students' environmental literacy. These findings have implications for incorporating innovative teaching methods to improve environmental education in schools. Highlight: Evaluates STEM-based PjBL for ecoliteracy in students. Uses purposive sampling for targeted research. Shows significant increase in ecoliteracy skills post-implementation. Keyword: STEM-based PjBL, Ecoliteracy, Quantitative Approach, Pre-experimental Methods, Environmental Education